1997
DOI: 10.1136/gut.40.5.664
|View full text |Cite
|
Sign up to set email alerts
|

Reduction in renal blood flow following acute increase in the portal pressure: evidence for the existence of a hepatorenal reflex in man?

Abstract: Background-To investigate the relation between changes in portal haemodynamics and renal blood flow (RBF) in patients with cirrhosis. Patients/Methods-Twenty patients with cirrhosis and transjugular intrahepatic portosystemic stent-shunts were divided into two groups which were well matched. At (RBF) and an increase in renal resistance.' 2 The reduction in RBF is accompanied by redistribution of intrarenal blood flow from the cortex to the medulla, even in patients without ascites,' and the hepatorenal s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
56
0
3

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 117 publications
(61 citation statements)
references
References 27 publications
2
56
0
3
Order By: Relevance
“…A similar splenorenal reflex also is observed in animal models with portal hypertension (30). Support for this concept in humans comes from the studies by Jalan et al (31), who demonstrated acute reduction in RBF in a patient with cirrhosis after acute transjugular intrahepatic shunt insertion (TIPS) occlusion. In another study, lumbar sympathectomy increased GFR in five patients with HRS and GFR Ͻ25 ml/min but not in three others with GFR Ͼ25 ml/min, suggesting that renal sympathetic nerve activity contributes to renal vasoconstriction in a selected group of patients with HRS (32).…”
Section: Stimulation Of the Renal Snsmentioning
confidence: 50%
“…A similar splenorenal reflex also is observed in animal models with portal hypertension (30). Support for this concept in humans comes from the studies by Jalan et al (31), who demonstrated acute reduction in RBF in a patient with cirrhosis after acute transjugular intrahepatic shunt insertion (TIPS) occlusion. In another study, lumbar sympathectomy increased GFR in five patients with HRS and GFR Ͻ25 ml/min but not in three others with GFR Ͼ25 ml/min, suggesting that renal sympathetic nerve activity contributes to renal vasoconstriction in a selected group of patients with HRS (32).…”
Section: Stimulation Of the Renal Snsmentioning
confidence: 50%
“…These flows are comparable with literature data. [18][19][20] Mean hepatic extraction of ICG was 0.288 Ϯ 0.049, which is higher than measured in patients with decompensated chronic and acute liver disease (0.054 Ϯ 0.085 21 ), supporting that our study population consisted of metabolically stable patients. In agreement, the body composition of the patients was similar to previous reports of patients with stable cirrhosis (Table 1).…”
Section: Resultsmentioning
confidence: 72%
“…27 In addition, increased portal and sinusoidal pressure can elevate sympathetic nerve activity to the heart and kidney via a hepatic baroreceptor-dependent mechanism. [42][43][44] Colombato et al documented that systemic (iliac) vasodilatation precedes the development of hyperdynamic circulation in the PVS rat. 39 This observation raises the possibility that the initiating event is a primary peripheral vasodilatation, which activates the CNS to increase cardiac output and induce further vasodilatation.…”
Section: Discussionmentioning
confidence: 99%